PENGARUH HARGA, PRODUK, PROMOSI, DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN BUKU DI CV GRAMERA - Sudarwati, Puji Triana, Bambang Mursito & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This research describe effect of product, price, promotion and distribution to purchasing decisions of book in CV Gramera Solo. Samples are taken from large consumer CV Gramera Solo which amounted to 35 agencies. This type of research uses quantitative research type, with convenience quoting sampling technique. Data obtained by spreading the questionnaire through CV sales. Gramera. The result of data analysis found that product, price, promotion and distribution have significant influence to purchasing decision simultaneously or partially. R2 result of 85,5%, while the rest of 14,5% influenced by other factor not included in this research.Keywords: price, product, promotion, distribution, purchase decision